Badibanga 2016. Mbororo, Invasion of a Nation - Taluah, Reginald Asangba (AAeO - Afrikanistik-Aegyptologie-Online, 2018)
Arthur Cimwanga Badibanga 2016. Mbororo, Invasion of a Nation. LAP Lambert Academic Publishing -  ISBN: 978-3-659-86375-2 ;  19,19 €